Higher Order Thinking Skills in Reading Questions of English Textbook for 10th Grade High School Students - Manalu, Sriwahyuni; Harahap, Neni Afrida Sari (Invention: Journal Research and Education Studies, 2025)
This study aimes at the implementation of Higher Order Thinking Skills (HOTS) in reading questions within the English textbook Bahasa Inggris: Work in Progress for 10th-grade high school students and how is the implementation of HOTS realized in the reading question of the English textbook? HOTS, as emphasized in Indonesia’s Curriculum, is critical for fostering students' analytical, evaluative, and creative abilities to meet 21st-century educational demands. The research employs descriptive qualitative method, data were collected through content analysis, categorizing reading questions based on Bloom’s Revised Taxonomy. A checklist table was used for classification, and the data were analyzed using the Miles & Huberman (1994) model, which includes data reduction, data display, and conclusion drawing. The results show that 58.3% of the questions fall under HOTS, while 41.7% are LOTS. Among HOTS, Analyzing (C4) is the most frequent, followed by Evaluating (C5) and Creating (C6). While the textbook includes HOTS-based questions, many still focus on factual recall, limiting students' critical thinking development. These findings suggest the need for curriculum improvements to ensure a more balanced integration of HOTS. This study provides insights for educators, policymakers, and textbook authors to enhance English instruction and align it with national educational goals.